2023
DOI: 10.3390/ijms24097888
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD1 Attenuates Acute Inflammation by Maintaining Mitochondrial Function in Macrophages via Interaction with VDAC1

Abstract: Over-activation of Toll-like receptor 4 (TLR4) is the key mechanism in Gram-negative bacterial infection-induced sepsis. SAM and HD domain-containing deoxynucleoside triphosphate triphosphohydrolase 1 (SAMHD1) inhibits multiple viruses, but whether it plays a role during bacterial invasion remains unelucidated. Monocyte-macrophage specific Samhd1 knockout (Samhd1−/−) mice and Samhd1−/− macrophage cell line RAW264.7 were constructed and used as research models to evaluate the role of SAMHD1 in TLR4-activated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Yang et al have shown that SAMHD1 interacts with the IKK complex to inhibit NF-κ B from being activated during the inflammatory response and viral infection [51]. SAMHD1 has also been shown to interact with VDAC1 to inhibit acute inflammation induced by LPS [52]. However, additional study is required to verify the miRNA-mRNA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al have shown that SAMHD1 interacts with the IKK complex to inhibit NF-κ B from being activated during the inflammatory response and viral infection [51]. SAMHD1 has also been shown to interact with VDAC1 to inhibit acute inflammation induced by LPS [52]. However, additional study is required to verify the miRNA-mRNA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The method as followed the previous article. 19 Cells were gathered and treated with lysis buffer. Equal amounts of total proteins (20 μg) were separated by sodium dodecyl sulfate‐polyacrylamide gel electrophoresis and transferred onto a polyvinylidene fluoride membrane (EMD Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…The method as followed the previous article. 19 Cells were gathered and treated with lysis buffer. Equal amounts of…”
Section: Western Blot (Wb)mentioning
confidence: 99%